Pendekatan Metode Statistical Process Control (SPC) untuk Meminimalisir Defect Produk Plastik di PT. BCD - Khozin, Achmad; Sulistyowati, Enik (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
Defective products are products that do not meet the quality specifications set by the company. The problem of defective products is very common in companies that produce goods, so it is important for companies to take steps to improve quality and reduce defects. Quality control is needed to reduce products that fall into the scrape category, which can result in losses. Analysis of defective products is carried out to find the cause, using quantitative statistical methods, namely Statistical Process Control (SPC). The highest type of defect data comes from torn plastic, followed by thin plastic, burnt plastic, melted plastic. Factors that affect product quality include machines, humans, materials, methods. Old machines can reduce productivity and cause defects. Human factors such as lack of operator concentration and hasty attitudes also affect defects. In addition, poor material quality and work methods that are not in accordance with procedures can cause problems in the production process. Companies need to improve the quality of raw materials and operator discipline to improve production results.